Uji Aktivitas Antibakteri Ekstrak Daun Jambu Air (Syzygium aqueum) : Sebuah Tinjauan Sistematis - Muhammad Ariq Naufal; Susianti Susianti; Suryani Agustina Daulay; Novita Carolia (Universitas Muhammadiyah Manado, 2024)
Indonesia is a country that dominated by tropical rainforests with adequate rainfall. These conditions allow various plant species to thrive. One such plant is water apple (Syzygium aqueum). The use of water apple leaf extract as an antibacterial agent has garnered attention due to the increasing trend of bacterial resistance againts antibiotics. The aim of this study is to describe the antibacterial effects of water apple (Syzygium aqueum) leaf extract on several bacterial species by observing the diameter of the inhibition zone. The method employed is a systematic review. Article searches were conducted through databases such as PubMed Central, ScienceDirect, Google Scholar, and Garuda. The journal selection and formulation of research questions were guided by the PICO method. Article searches followed the 2020 PRISMA methodology. The article search yielded six articles reviewed from a total of 9,911 articles identified. The findings from the reviewed articles indicate that water apple leaf extract (Syzygium aqueum) exhibits antibacterial effects on both gram-positive and gram-negative bacteria. The active compounds in water apple leaf extract that exhibit antibacterial properties are flavonoids, terpenoids, saponins, tannins, and alkaloids.